2010
DOI: 10.1523/jneurosci.1784-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Dysfunction and Cognitive Impairments Provoked by Chronic Early-Life Stress Involve Excessive Activation of CRH Receptors

Abstract: Chronic stress impairs learning and memory in humans and rodents and disrupts long-term potentiation (LTP) in animal models. These effects are associated with structural changes in hippocampal neurons, including reduced dendritic arborization. Unlike the generally reversible effects of chronic stress on adult rat hippocampus, we have previously found that the effects of early-life stress endure and worsen during adulthood, yet the mechanisms for these clinically important sequelae are poorly understood. Stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
420
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 375 publications
(453 citation statements)
references
References 67 publications
(110 reference statements)
29
420
4
Order By: Relevance
“…Although drug treatments tackling CRHR1 have been envisioned as potentially promising anxiolytic and antidepressive drugs (Kunzel et al, 2003;Refojo and Holsboer, 2009), recent evidence in rodents suggests that they could also be effective in modifying not only actual pathological manifestations at adulthood but also the developmental trajectories linking early adversity to adult psychopathology. These rodent studies showed that exposure to stress during the two first postnatal weeks leads to increased central CRH and CRHR1 expression, and altered a number of behaviors in tests of emotion and cognition (Plotsky et al, 2005;Ivy et al, 2010;Wang et al, 2011Wang et al, , 2012. Importantly, they also found that some of the long-term behavioral alterations could be reversed by inhibiting CRHR1 function (e.g., through CRHR1 antagonist treatment or conditional forebrain CRHR1 knockout) in the developmental period occurring immediately after early life stress (Ivy et al, 2010;Wang et al, 2011Wang et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although drug treatments tackling CRHR1 have been envisioned as potentially promising anxiolytic and antidepressive drugs (Kunzel et al, 2003;Refojo and Holsboer, 2009), recent evidence in rodents suggests that they could also be effective in modifying not only actual pathological manifestations at adulthood but also the developmental trajectories linking early adversity to adult psychopathology. These rodent studies showed that exposure to stress during the two first postnatal weeks leads to increased central CRH and CRHR1 expression, and altered a number of behaviors in tests of emotion and cognition (Plotsky et al, 2005;Ivy et al, 2010;Wang et al, 2011Wang et al, , 2012. Importantly, they also found that some of the long-term behavioral alterations could be reversed by inhibiting CRHR1 function (e.g., through CRHR1 antagonist treatment or conditional forebrain CRHR1 knockout) in the developmental period occurring immediately after early life stress (Ivy et al, 2010;Wang et al, 2011Wang et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…These rodent studies showed that exposure to stress during the two first postnatal weeks leads to increased central CRH and CRHR1 expression, and altered a number of behaviors in tests of emotion and cognition (Plotsky et al, 2005;Ivy et al, 2010;Wang et al, 2011Wang et al, , 2012. Importantly, they also found that some of the long-term behavioral alterations could be reversed by inhibiting CRHR1 function (e.g., through CRHR1 antagonist treatment or conditional forebrain CRHR1 knockout) in the developmental period occurring immediately after early life stress (Ivy et al, 2010;Wang et al, 2011Wang et al, , 2012. So far, all those studies involved maternal stress during the first two postnatal weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations